2018
DOI: 10.17323/1814-9545-2018-4-139-166
|View full text |Cite
|
Sign up to set email alerts
|

Learning Analytics in Massive Open Online Courses as a Tool for Predicting Learner Performance

Abstract: Быстрова Татьяна Юрьевна — доктор философских наук, профессор Уральского гуманитарного института. E-mail: taby27@yandex.ruЛарионова Виола Анатольевна — кандидат физико-математических наук, доцент, заместитель проректора, заведующий кафедрой Высшей школы экономики и менеджмента. E-mail: v.a.larionova@urfu.ruСиницын Евгений Валентинович — доктор физико-математических наук, профессор Высшей школы экономики и менеджмента. E-mail: e. v.sinitcyn@urfu.ru.Толмачев Александр Владимирович — старший преподаватель Высшей … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Intelligent content recommendation systems use artificial intelligence methodologies to provide tailored educational resources that align with the preferences and objectives of individual learners (Zhang et al, 2020). The use of AI-powered data-driven learning analytics allows educators to extract valuable insights from learner data (Bystrova et al, 2018), which can be utilised to inform instructional strategies and facilitate continuous improvement. (Troussas et al, 2019) The advancements that have been made in technology have had a substantial impact on education (See et al, 2021), resulting in improved learner involvement (McDonald et al, 2014), acquisition of knowledge(Al-Emran & Teo, 2019), and academic achievements in the era of digitalization (Adi et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Intelligent content recommendation systems use artificial intelligence methodologies to provide tailored educational resources that align with the preferences and objectives of individual learners (Zhang et al, 2020). The use of AI-powered data-driven learning analytics allows educators to extract valuable insights from learner data (Bystrova et al, 2018), which can be utilised to inform instructional strategies and facilitate continuous improvement. (Troussas et al, 2019) The advancements that have been made in technology have had a substantial impact on education (See et al, 2021), resulting in improved learner involvement (McDonald et al, 2014), acquisition of knowledge(Al-Emran & Teo, 2019), and academic achievements in the era of digitalization (Adi et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…MOOC research methods (Cluster 5): This cluster indicated that learning analytics was the central keyword, followed by machine learning, content analysis, social network analysis and educational data mining. The publications on implementation of learning analytics in MOOCs (see Bystrova et al, 2018;Yulianto et al, 2018) showed that emerging research methods are used to predict learners' probability of drop out and success, and their performance.…”
Section: Social Network Analysis Of the Abstractmentioning
confidence: 99%
“…Massive Open Online Courses (MOOCs) are a relatively recent aspect of ITS research, and we identify our earliest instance of this within our corpus in 2013 [38]. We identify 38% of research in this topic entailing learning analytics [39] [40] [41], which involves the wealth of data provided by MOOC platforms. This data may be applied to dropout prediction and forecasting of MOOC platforms [42] [43], and we identify 11% of documents involving dropout prediction.…”
Section: Topic 12 -Moocsmentioning
confidence: 99%